Analisis Kajian Literatur mengenai Aspek-Aspek Kelayakan Bisnis dalam Industri Kopi - Awal Fitriyana; Sofiaturohmah, Alis; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine the business feasibility in the coffee industry through a literature review approach that identifies various factors influencing the sustainability and growth of coffee businesses. The coffee industry in Indonesia has significant potential, but challenges in economic, social, cultural, and regulatory aspects need to be understood by business players. The study employs a qualitative approach with a literature review method, covering various aspects of business feasibility, such as market analysis, marketing strategies, financial aspects, and risk management. The findings reveal that business feasibility in the coffee industry is highly influenced by factors such as high market demand, product diversity, and challenges in human resource management and effective marketing. The study also highlights the importance of alignment with government regulations and sustainable practices in maintaining product quality. By understanding business feasibility aspects, coffee industry players can design more effective strategies to ensure success and competitiveness in the market.